2020
DOI: 10.1186/s12864-019-6400-z
|View full text |Cite|
|
Sign up to set email alerts
|

Whole genome sequencing and phylogenetic analysis of human metapneumovirus strains from Kenya and Zambia

Abstract: BackgroundHuman metapneumovirus (HMPV) is an important cause of acute respiratory illness in young children. Whole genome sequencing enables better identification of transmission events and outbreaks, which is not always possible with sub-genomic sequences.ResultsWe report a 2-reaction amplicon-based next generation sequencing method to determine the complete genome sequences of five HMPV strains, representing three subgroups (A2, B1 and B2), directly from clinical samples. In addition to reporting five novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, included studies suggest that different sequencing methods can assist researchers in achieving different purposes, in addition to selecting an appropriate NGS platform. In light of the studies reviewed, researchers usually employed the PCR amplicon sequencing method when they performed the evolutionary or epidemiological analysis of one target respiratory virus, especially during outbreaks 53,80,86 . This method could enable researchers to analyse the genomes of epidemic‐prone viruses in a quick way and detect mutations/variants, which may be beneficial for future drug and vaccine improvement or development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, included studies suggest that different sequencing methods can assist researchers in achieving different purposes, in addition to selecting an appropriate NGS platform. In light of the studies reviewed, researchers usually employed the PCR amplicon sequencing method when they performed the evolutionary or epidemiological analysis of one target respiratory virus, especially during outbreaks 53,80,86 . This method could enable researchers to analyse the genomes of epidemic‐prone viruses in a quick way and detect mutations/variants, which may be beneficial for future drug and vaccine improvement or development.…”
Section: Discussionmentioning
confidence: 99%
“…The additional advantages of these Nanopore sequencers include their portability in field studies, low initial installation costs, and simple library preparation procedure with the minimum laboratory equipment requirements. 40,56,61,[83][84][85] 53,80,86 This method could enable researchers to analyse the genomes of epidemic-prone viruses in a quick way and detect mutations/variants, which may be beneficial for future drug and vaccine improvement or development. Aside from that, researchers also utilised the PCR amplicon WGS method when they attempted to reveal transmission events of the virus (e.g., IFVs and SARS-CoV-2).…”
Section: Barriers To the Routine Use Of Ngs In Clinical Laboratoriesmentioning
confidence: 99%
“…HMPV became a part of infectious disease genomic surveillance after development of whole-genome tiled amplicon sequencing technology. This methodology allowed the identification of two major phylogenetic subtypes of HMPV, each containing two sublineages (A1, A2, B1, B2) [83,84]. The use of this new knowledge in vaccine manufacturing led to multi-viral vaccine research and development.…”
Section: Combination Vaccines Against Parainfluenza Type 3 Virus (Piv...mentioning
confidence: 99%
“…Recent genetic changes, such as sequence duplications in the HMPV G gene, highlight the importance of monitoring HMPV evolutionary dynamics, but partial genome sequencing will miss any evolutionary events that occur in genes other than F and G. With next-generation sequencing (NGS) platforms rapidly improving, obtaining viral whole-genome sequences has simplified considerably ( 22 ). Recent studies reported assays for HMPV whole-genome sequencing using Illumina sequencing, Ion Torrent, or Nanopore technology ( 23 26 ). We recently introduced an HMPV whole-genome sequencing method using MinION Nanopore technology ( 27 ).…”
Section: Introductionmentioning
confidence: 99%